Digital Disruption in the COVID-19 Era : The Impact on Learning and Students' Ability to Cope with Study in an Unknown World. - James, Trixie; Toth, Gabriela; Tomlins, Melissa; Kumar, Brijesh; Bond, Kerry (Student Success v.12 n.3 p.84-95 https://doi.org/10.5204/ssj.1784, 2021)
The COVID-19 pandemic will forever be known as a disruptive dilemma that impacted many industries in Australia. For the university sector, sudden lockdown and social distancing rules resulted in an acceleration in the provision of learning and teaching via online platforms, creating new challenges for students and educators. This project explored the ways in which an enabling course supported students through the forced transition from face-to-face classes to online learning due to the COVID-19 restrictions, and the students' ability to adjust to the disruption caused by the pandemic. This unexpected change provided the opportunity to explore how enabling students perceived this experience and the effect it had on their ability to complete their units of study. This paper presents findings on the impact that the abrupt transition to online learning had on the students' educational experience and on their psychological and emotional wellbeing. It was found that most students experienced increased stress due to the changes in household dynamics, responsibilities and a different learning context, yet many reported improved study and technological skills, as well as an improved awareness of their ability to cope with change. [Author abstract]